2020
DOI: 10.3390/sym12101647
|View full text |Cite
|
Sign up to set email alerts
|

On Aluminum Honeycomb Impact Attenuator Designs for Formula Student Competitions

Abstract: The use of impact attenuators (IA) is important for vehicles as they absorb the kinetic energy exerted from the car crashes to protect the drivers from any possible injuries. Under the framework of the Formula Student (FS) competition, we investigate various designs of IA made of aluminum honeycomb material. Specifically, the crushing behavior of the honeycomb structure is investigated from the theoretical point of view and later verified with numerical simulations. To achieve the desired crushing behavior of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…The behaviour of spring was built based on art. [17]: The mean value has been found to be in accordance with experimental data. The simulation is able to predict the values of absorber crushing (honeycomb), mean collapsing force, and mean acceleration registered on rigid plate (see figure 8) with wing lumped mass hypothesis.…”
Section: Absorber Numerical Characterizationsupporting
confidence: 83%
“…The behaviour of spring was built based on art. [17]: The mean value has been found to be in accordance with experimental data. The simulation is able to predict the values of absorber crushing (honeycomb), mean collapsing force, and mean acceleration registered on rigid plate (see figure 8) with wing lumped mass hypothesis.…”
Section: Absorber Numerical Characterizationsupporting
confidence: 83%
“…The energy absorption characteristics and dynamic evolution process have concluded that the combined structure honeycomb has a stronger energy absorption effect under the same conditions. Quoc [17] studied the crushing behavior of the honeycomb structure from a theoretical perspective and then verified it by numerical simulation. Mertani [18] conducted an experimental study on the compression response of a hexagonal honeycomb core from an initial elastic state to a fully crushed state.…”
Section: Introductionmentioning
confidence: 97%
“…NASA and others [ 2 , 3 , 4 ] concluded that the honeycomb structure has the best energy-absorbing properties in relation to its specific mass. Due to this feature, honeycomb structures are used across a wide range of industries, including the automotive industry [ 5 , 6 ] and the military [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%